The Problems of Application Art. 208 of Civil Procedure Code of the Russian Federation - Dmitriy Nikolaevich Polyakov (Сибирское юридическое обозрение)
In this article the author explains the conception of exacted money indexation. At the same time this conception is analyzed with an allowance for problems which appear while considering applications in accordance with Art. 208 of the Civil Procedure Code of the Russian Federation. It concerns also the terms of indexation (initial and final) and the possibility of "double" indexing and using the principle of debtor's culpability.